PENCEGAHAN BANJIR, DAN PENURUNAN MUKA AIR TANAH DENGAN SUMUR RESAPAN - Setiabudi, Bambang (Universitas Diponegoro, 2009)
Abstract Â Bambang Setiabudi, in paper floods and to discharge of ground water many created in much housing district. That case to appoint often to created every year at rainy season and dry season Expedient to doing is by absorbtion well. Absorbtion ,well is water conservation technology to resemble well with to be certain depth for to catch of water.